Exploring the Best Practices in Teaching Filipino 6 at Southeast Butuan District: Basis for a Proposed Enhancement of Learning Action Cell (LAC) Sessions - Villamor, Bryan R.; Giducos, Romeo (Randwick International of Education and Linguistics Science Journal, 2025)
This phenomenological study explored the best practices of teaching Filipino 6 in Southeast Butuan District, Philippines, during the S.Y 2024-2025. Six experienced Filipino 6 teachers, recognized for their expertise, were purposively selected within the district. Data were gathered through semi-structured interviews with the teachers, focusing on their classroom management, lesson preparation, lesson delivery, utilization of instructional materials and assessment. Additionally, focus group discussions were conducted with students to gain insights into their perceptions of the teachers' practices. Thematic analysis was employed to analyze the qualitative data, revealing key themes related to effective teaching practices in Filipino 6. The Study found that experienced Filipino 6 teachers in the district demonstrate a strong understanding of effective pedagogical practices. These practices include creating a conducive learning environment, establishing clear rules and expectations, maintaining a clean and organized classroom, providing regular feedback, preparing well-structured lesson plans aligned with curriculum standards, and employing diverse teaching strategies to engage students, utilizing learning materials and measure learning through valid and reliable assessment. Notably, there was a clear alignment between teacher practices and student perceptions, indicating that students are actively aware of and positively influenced by their teachers' efforts to create a structured and supportive learning environment. Based on the findings, a district-wide policy is proposed to monitor and enhance best practices through orientations, classroom observations, and continuous professional development for teachers. This policy aims to promote the use of technology, encourage collaboration among the teachers, and to ensure effective learning experience for all students in the district.